Positive cyberpsychology as a field of study of the well-being of people interacting with and via technology - Fortuna, Paweł (Frontiers in Psychology, 2023)
The aim of the article is to postulate introducing and developing positive cyberpsychology (PCyb) as a subdiscipline of cyberpsychology, which emerges at the intersection of cyberpsychology, positive psychology, and well-being informed design, and focuses on studying determinants of human well-being through interactions with and via technology. The article presents the rationale for considering the emergence of PCyb based on the importance of research on the positive transformation of people in the era of progressive digitalization and cyborgization, and the growing partnership of cyberpsychology, positive psychology, and well-being informed design in the form of paradigms and ongoing research. Moreover, it highlights the need to reframe cyberpsychology dominated by the study of the "dark side" of technology and the need to integrate and increase the "visibility" of research results on the beneficial effects of technology. The article also accentuates the opening perspective of a more in-depth analysis of the positive transformation process than the one existing within the well-being informed design and underlines a broader plan of innovation use than is taken into account in cyberpsychology and positive psychology. Lastly, it discusses the use of the results of research conducted within PCyb in the design of new technologies, consulting, and education, as well as the possibility of strengthening the voice of psychologists in the debate about the future of humans functioning in the constantly changing technosphere.